THE INFLUENCE OF INVESTMENT ON THE INNOVATIVE DEVELOPMENT OF RUSSIAN REGIONS - D. Y. Fraimovich (Финансы: теория и практика, 2017)
Article Retracted. In our country the implementation of regional investment projects very often generates problems of the qualitative monitoring of their effectiveness, and thus makes it impossible to use existing innovative potential of social and economic systems to full extent. The paper suggests the approaches to assess the impact of different types of investment resources on the innovative regional development. For these purposes, regions have been ranked according to the indicator of their innovation susceptibility to investments in fixed assets. The study identifies the Federal District subjects which are low performers in initiating the process of high-tech manufacturing. The paper sets out conditions for attracting domestic and foreign investments in the regional innovation projects. Suggested assessment mechanisms can be used by federal and regional authorities as an effective management tool in developing, implementing and monitoring innovation and investment programs aimed at country’s modernization.